BETWEEN SHARIA AND CITIZENSHIP: Political Thought of Muslim Minorities in the Contemporary Asia-Pacific - Haryono, Dodi (Asia-Pacific Journal on Religion and Society, 2024)
This article explores the transformation of political thought among Muslim minority communities in the Asia-Pacific region since the early 2000s, particularly in relation to the interplay between religion (Sharia) and the state. Amid global currents of Islamophobia, exclusive nationalism, and accelerating globalization, Muslim minorities in countries such as India, the Philippines, Southern Thailand, Singapore, Australia, and New Zealand have demonstrated a shift in orientation—from pursuing Islamic statehood to embracing inclusive citizenship strategies. Employing a qualitative-descriptive approach with political discourse analysis and cross-national comparative methods, this study finds that Sharia is increasingly reinterpreted as a set of public ethical norms. Simultaneously, Muslim political engagement is directed more toward advocating civil rights, democratic participation, and collective identity recognition within secular state frameworks. The article argues that Muslim minorities are not merely objects of state policies but transformative agents who articulate an Islamic ethics of citizenship within pluralistic contexts. These findings enrich the field of Islamic political studies by offering perspectives from the margins that are contextually grounded, ethically nuanced, and relevant to the future of multicultural societies.